2003
DOI: 10.1074/jbc.m308700200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Progenitor Cell Fusion by ABCB5 P-glycoprotein, a Novel Human ATP-binding Cassette Transporter

Abstract: Cell fusion involving progenitor cells is a newly recognized phenomenon thought to contribute to tissue differentiation. The molecular mechanisms governing cell fusion are unknown. P-glycoprotein and related ATP-binding cassette transporters are expressed by progenitor cells, but their physiological role in these cell types has not been defined. Here, we have cloned ABCB5, a rhodamine efflux transporter and novel member of the human P-glycoprotein family, which marks CD133-expressing progenitor cells among hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
270
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(283 citation statements)
references
References 50 publications
9
270
2
2
Order By: Relevance
“…66 Reasoning an ABC transporter that had been newly cloned, ABCB5 (ATPbinding cassette, subfamily B, member 5), might hold the key to understanding progenitor cell fusion; it was found that ABCB5 marks CD133 þ progenitor skin melanocytes and also determines the propensity for fusion. 43 Furthermore, ABCB5 expression was detected in cells from an established human melanoma cell line. Thus, by defining a molecular mechanism for stem cell fusion that resulted in cell growth and differentiation, the stage was set for determining the potential relevance of this marker to human melanoma.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…66 Reasoning an ABC transporter that had been newly cloned, ABCB5 (ATPbinding cassette, subfamily B, member 5), might hold the key to understanding progenitor cell fusion; it was found that ABCB5 marks CD133 þ progenitor skin melanocytes and also determines the propensity for fusion. 43 Furthermore, ABCB5 expression was detected in cells from an established human melanoma cell line. Thus, by defining a molecular mechanism for stem cell fusion that resulted in cell growth and differentiation, the stage was set for determining the potential relevance of this marker to human melanoma.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
“…43 At the time it was known that co-culture of pluripotent embryonic and mesenchymal stem cells with lineagecommitted cell types produced hybrids as a result of cell fusion, and that these hybrids could generate differentiated progeny in vitro and in vivo. [44][45][46][47][48] Although such fusion events were thus considered to represent a model whereby progenitor cells express plasticity and renewal, the mechanism for this process was unknown.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs have been identified in a number of cancers including acute myeloid leukaemia (AML) (Bonnet and Dick, 1997;Passegue et al, 2003), glioblastoma (Singh et al, 2003), breast (Al-Hajj et al, 2003;Ponti et al, 2005), lung (Kim et al, 2005), prostate (Collins et al, 2005), ovarian (Bapat et al, 2005), gastric (Houghton et al, 2004), esophagous ( Li et al, 2013 ), Head and Neck SCC (Satpute et al, 2013) and skin cancers (Frank et al, 2005;Monzani et al, 2007). Different markers have been identified to be expressed on melanoma stem cells (Quintana et al, 2010;Shakhova and Sommer, 2013) comprising CD20 (Fang et al, 2005) and ABC transporter family members such as MDR1, ABCG2 and ABCB5 (Frank et al, 2003;Frank et al, 2005;Monzani et al, 2007;Keshet et al, 2008;Schatton et al, 2008), CD271 (Boiko et al, 2010;Civenni et al, 2011), CD44 (Fernandez-Figueras et al, 1996, CD133 (Klein et al, 2006) and Nestin (Piras et al, 2010;Fusi et al, 2011). Among these markers, CD133 and Nestin have been described as markers of melanocytic stem cells and two of the most important surface markers with increased expression in the cancer stem cell fraction in different human malignancies, including melanoma (Klein et al, 2006;Monzani et al, 2007;Rappa et al, 2008;Al Dhaybi et al, 2010;Shakhova and Sommer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Szintén a tumorőssejt-hipotézis mellett szól, hogy az említett sejtklónokon olyan jellegzetes sejtfelszíni markerek expresszálódnak, amelyek az embrionális vagy szomatikus őssejtekre jellemzők. A tumorőssejtek nem feltétlenül a szomatikus őssejtek onkogén transzformációjából származnak, hanem létrejöhet-nek a szöveti sejtekben bekövetkező génmutációk és génexpressziós változások következtében, vagy akár tumoros sejtek differenciált sejtekkel és őssejtekkel való fú-ziójával is [14].…”
Section: öSszefoglaló Közleményunclassified